A neural network predictive control method for power control of small pressurized water reactors. (May 2022) - Xiao, Kai; Wu, Qiaofeng; Chen, Jie; Pu, Xiaofei; Zhang, Ying; Yang, Pengcheng
Highlights: A neural network predictive (NNP) power control method is proposed for small PWRs. A global NNP power controller is designed for a small PWR based on the core multi-model. The NNP power controller has good performances at different power levels. Abstract: Compared with large pressurized water reactors (PWRs), small PWRs have flexible operating conditions and complex operating environment, putting forward higher requirements on the power control system. Considering the low model identification accuracy of the widely-used model predictive control algorithm in reactor control, a neural network predictive (NNP) power control method is proposed for small PWRs in this paper. The local models under five typical operating conditions are weighted by a multi-model method to establish a core multi-model system, based on which a global NNP power control system is designed. The neural network is used to identify the core model first, and then a performance criterion function is optimized to determine the optimal control input to the reactor core. Simulation results of a small PWR core under typical transient conditions demonstrate the good load-following performance and strong anti-interference capability of the proposed NNP power control method for small PWRs.